Research progress of rare earth zirconate thermal barrier coating ceramic materials - Yin, Qiang; Shen, Ke-Hui; Wang, Yan; Xing, Ya-Zhe (Materials today communications, 2025)
As aviation engines continue to advance toward higher efficiency and greater thrust-to-weight ratios, the demand for improved performance of the thermal barrier coatings (TBCs) on their hot-end components becomes increasingly pressing. Traditional YSZ thermal barrier coatings are susceptible to phase transformation and sintering under elevated temperatures and complex operating conditions. To meet future needs for advanced aviation engines, new ceramic thermal barrier coatings must be developed promptly. Among many new ceramic materials for thermal insulation coatings, rare earth zirconate (RE2Zr2O7) has received much attention because of its high oxygen void concentration, controllable crystal structure, stable high-temperature phase, less thermal conductivity compared to YSZ, and high corrosion resistance. This review comprehensively summarizes the recent research progress of RE2Zr2O7 in terms of crystal structure, thermal physical properties, mechanical properties, and corrosion resistance. The effects of doping ions and preparation process on its crystal structure are discussed. The effects of rare earth element doping, high-entropy design, and second-phase composite on the thermal physical and mechanical properties of RE2Zr2O7 are explored. Finally, a detailed review of the corrosion behavior of RE2Zr2O7 under molten deposit action is provided, with corresponding protective measures proposed from the perspectives of rare earth element doping, nanostructure design, and composition regulation. [Display omitted]